Perancangan Database Pada Sistem Asessmen Dan Pemetaan Hasil Asessmen Berbasis Tag Sebagai Pembantu Penyusunan Strategi Pembelajaran - Apriliya Kurnianti; Angguningtyas Angguningtyas; Reza Giga Isnanda (Universitas Muhammadiyah Yogyakarta, 2017)
The Assessment and Mapping System of Tag-Based Assessment Results is an online-based system that aims to assist teachers and students in recording and mapping the assessment results for college admission. Information from the recording and mapping is very useful in helping the preparation of learning strategies and strategies to face the next exam. To support this assessment system required a database design. In the design of the database, the design is divided into 4 stages of Data Collection and Analysis, Conceptual Database Design, Logical database design, and Physical Database Design. The design of a conceptual database includes anyone involved in the system, what inputs are required, and what information (output) is desired from the database. While in logical database design, including the determination of Entities and attributes, determination of primary key, Entity Relationship Diagram (ERD). In the physical design, including ERD conversion to table form, normalization and implementation into the form of tables created on MS SQL Server. From the design of the database produces tables without anomalies, ie Eye, Student, Teacher, Testing, Problem, StandardValues, Tags, Groups, GrupMember, Member, EventUjian, Nilai, NomorSoal, PesertaUjian, Clipbooard, and OnGoingExam tables.